2022
DOI: 10.48156/1388.2022.1917166
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for widespread gene flow and migration in the Globe Skimmer dragonfly Pantala flavescens

Abstract: The global population structure and dispersal patterns of Pantala flavescens (Fabricius, 1798) are evaluated using a geographically extensive mitochondrial DNA dataset, a more limited samples of nuclear markers, wing isotopic (δ²H) data and a literature review. No spatial or temporal haplotype structure was recovered between the samples. Isotope data suggest that most samples were immigrants at the collection locations. A literature review of migration events for the species confirms regular inter-and intra-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…These species are extremely variable in their natural histories. P. pennipes and I. elegans are highly territorial odonates with relatively limited vagility, while P. flavescens is considered the global wanderer, given their globally panmictic population, with individuals potentially crossing oceans (Ware et al, 2022). Further, these 3 species are all relatively young lineages from species rich families (Kohli et al, 2021;Suvorov et al, 2021).…”
Section: P Pennipes Has Retained the Putative Ancestral Karyotype (2n...mentioning
confidence: 99%
“…These species are extremely variable in their natural histories. P. pennipes and I. elegans are highly territorial odonates with relatively limited vagility, while P. flavescens is considered the global wanderer, given their globally panmictic population, with individuals potentially crossing oceans (Ware et al, 2022). Further, these 3 species are all relatively young lineages from species rich families (Kohli et al, 2021;Suvorov et al, 2021).…”
Section: P Pennipes Has Retained the Putative Ancestral Karyotype (2n...mentioning
confidence: 99%
“…It makes long transcontinental and trans-oceanic migrations [23,24], and is frequently found in warmer regions, particularly in the tropics, but is found in temperate regions in the summer [25]. Though it is nNot surprisingly-given the migratory nature of the species-evidence suggests widespread gene flow between populations across the globe, and it may be appropriate to refer to many, if not all, of the migratory sub-populations as panmictic [24]. An smc++ [26] analysis, using individuals from Guangdong Province, China found that the effective population size of P. flavescens has varied between 1 million and 10 million individuals over the last million years, with declines associated with the onset of the agricultural and industrial period [27].…”
Section: Pachydiplax Longipennis (Libellulidae)mentioning
confidence: 99%
“…Hypothesis 7: migratory dragonflies can more efficiently process carbohydrates. In P. flavescens, the expansion of gene families related to the carbohydrate metabolic process are a plausible mechanism for allowing this species to undertake trans-oceanic and trans-continental migrations in a single generation [24]. It is likely that an especially efficient process for obtaining energy from carbohydrates would be selected for on such long migrations.…”
Section: Gene Birth/death Ratementioning
confidence: 99%
“…Pantala flavescens is probably the only species capable of consistent transoceanic dispersions without the aid of humans. Its amazing gliding abilities, together with a very fast larval cycle [77] and its adaptation to become dormant enabling it to survive drought conditions [78], make it the most widespread Odonata species in the world [79].…”
Section: General Diversity Patternsmentioning
confidence: 99%